Transformational Leadership Role in Human Resource Effectiveness - Gunawan Gunawan; Rhian Indradewa; Tantri Yanuar Rahmat Syah; Diana Fajarwati (Penerbit Kemala Indonesia, 2020)
This study aims to determine the relationship of transformational leadership with knowledge codification strategies. Here, transformational leadership with personalization strategies knowledge has codification relationship strategies with human capital and personalization strategies (effectiveness of human resources). In this study, we used quantitative data and structural equation modelling techniques to test the model. The confirmation factor analysis is performed to check internal reliability and data validity. Besides, the questionnaire form was adopted from previous literature. The results show a hypothesis testing with a real level of 0.05 obtained p-value of 0.000